PENURUNAN JUMLAH CACAT PRODUK PADA MESIN INSULATING DENGAN METODE FAILURE MODE EFFECT ANALYSIS - Rochmoeljati, R (Jurnal Teknik Industri, 2008)
In the world of defect industry represent problems which need to be paid attention by defect which company later will have an effect on to many at least got profit company.. This company face problems how to decrease percentage of handicap at one of their product, that is NYAF kabek which relative still big that is equal to 4.13% from totalizing result of production. Existences of high request to this product oblige company to apply system repair of quality. This action is done at defect that happened at cable production process of NYAF. Pursuant to result of research, have been got degradation of amount of defect cable production process of NYAF counted 0.91% from 4.13% (with amount of defect 11.200 totally output counted 271.015) becoming 3.22% (amount of defect 3.840 totally output counted 119.156). With existence of the result, please prove that FMEAP can become appliance to company to do repair chronically.